Being Neighbor in the Coming Pandemic Crisis: Thinking with Luther in the 21st Century - Simpson, Gary M. (Word & world, 2020)
Human history has regularly recorded the appearances of pandemic-type illnesses that spread across human populations. The responses to these incidents need to go beyond medical care, as the fear and social upheavals possible in such times call as well for a theological and ethical response on the part of social and religious leaders.